Can new immunoassay techniques improve bladder cancer diagnostics With protein biomarkers? - Shlyapnikov, Yuri M.; Malakhova, Ekaterina A.; Vinarov, Andrey Z.; Zamyatnin, Andrey A.; Shlyapnikova, Elena A. (Frontiers in Molecular Biosciences, 2021)
The search for new diagnostic tests for cancer or ways to improve existing tests is primarily driven by the desire to identify the disease as early as possible. In this report, we summarize the current knowledge of the most promising diagnostic protein bladder cancer (BC) markers reported over the last decade. Unfortunately, analysis of published data suggests that a reliable, highly sensitive biomarker test-system based on ELISA for detecting BC has not yet been developed. The use of more sensitive assays detecting ultra-low concentrations of biomarkers not available for ELISA could be very beneficial. Based on the literature and pilot experimental data, we conclude that a highly sensitive immunoassay using microarrays and magnetic labels could be an effective and cheap technique suitable for the detection of diagnostically relevant BC biomarkers.